ANALYSIS OF THEORETICAL AND METHODOLOGICAL CONCEPTS FOR ASSESSING FOOD SECURITY - Assel Zhumaevna Zhunussova; Baglan Mukhamedzhanovna Serikbayeva; Aliya Mukhamedzhanovna Utegenova (Academics and Science Reviews Materials, 2025)
This article analyzes the assessment of food security at the national and regional levels based on the components of accessibility, considering the spectrum of income and expenditure analysis of the population. The results confirm the relevance of the food security issue for Kazakhstan and its regions. The study examines the country's level of development, the relationship between household expenditures on food products within the total expenditure structure and income levels, and presents a comprehensive analysis of national food security.